Feasibility of Anesthesiologist-Performed Preoperative Echocardiography for the Prediction of Postinduction Hypotension: A Prospective Observational Study - Babar Fiza; Neal Duggal; Caitlin E. McMillan; Graciela Mentz; Michael D. Maile (Anesthesiology Research and Practice)
Purpose. To determine if left ventricular or inferior vena cava (IVC) measurements are easier to obtain on point-of-care ultrasound by anesthesiologists in preoperative patients, and to assess the relationship between preoperative cardiac dimensions and hypotension with the induction of general anesthesia. Methods. This prospective observational study was conducted at a large academic medical center. Sixty-three patients undergoing noncardiac surgeries under general anesthesia were enrolled. Ultrasound examinations were performed by anesthesiologists in the preoperative area. To ensure that hypotension represented both a relative and absolute decrease in blood pressure, both a mean arterial pressure (MAP) < 65 mmHg and a MAP decrease of >30% from preoperative value defined this outcome. Results. Left ventricular measurements were more likely to be acquired than IVC measurements (97% vs. 79%). Subjects without adequate images to assess IVC collapsibility tended to have a higher body mass index (33.6 ± 5.5 vs. 28.5 ± 4.5, p=0.001). While high left ventricular end-diastolic diameter values were associated with a decreased odds of MAP < 65 mmHg (OR: 0.24, 95% CI: 0.07–0.83, p=0.023) or a MAP decrease of >30% from baseline alone (OR: 0.25, 95% CI: 0.07–0.83, p=0.023), the primary endpoint of both relative and absolute hypotension was not associated with preoperative left ventricular dimensions. Conclusions. Preoperative cardiac ultrasound may be a more reliable way for anesthesiologists to assess patients’ volume status compared to ultrasound of the IVC, particularly for patients with a higher body mass index.